Mengelola Tantangan dan Peluang dalam Bisnis Reseller Online: Strategi Pemasaran, Manajemen Risiko, dan Pengelolaan Keuangan - Hilmi Satria Himawan; Putri Nor Avilla; Riana Amanda; Siti Zaira (Jurnal Visi Manajemen, 2025)
In the rapidly evolving digital era, online commerce has become a phenomenon that dominates the business world. One important aspect of the online trade ecosystem is the role of resellers. Online shop resellers have become a vital element that connects producers or product owners with end consumers through digital platforms. Resellers act as intermediaries that bridge the process of product distribution from its source to the hands of consumers. The main issues include marketing competition, unilateral product cancellations by customers, and defective or incorrect items. The research question used by how online shop resellers overcome business competition challenges in the era of digitalization? This research adopts a qualitative approach using field study methods. This research concludes that operating as an online shop reseller involves several risks, and to address these challenges, various improvements can be made in marketing techniques, risk management implementation, and cash flow recording techniques to overcome the ambiguity of profits generated in the online reseller business.